Reforma a La Ley General De Instituciones del Sistema Financiero para el manejo de los depósitos de ahorros en las entidades financieras controladas por la superintendencia de bancos - Yasbek Granda, Joffre Oswaldo (2015)
This investigation is named “Reform to the General Law of Financial Institutions for the management of the savings deposits in the Financial Institutions controlled by the Superintendence of Banks”, which was done following the guidelines for the investigations of Universidad Nacional de Loja, At-distance Modality. The main objective for this investigation is to do a juridical, critical and doctrinaire research of the General Law of the Financial Institutions and the Monetary and Financial Organic Code, in order to propose the incorporation of legal dispositions which regulate the management of the savings deposits, target that is aimed with the proposal formulated at the end of this work, considering as a basis the juridical analysis about this topic in which is stated my own criterion about some topics which are the source to formulate the legal reforms. The juridical analysis is complemented with the in-situ investigation which is supported by the surveys applied to experienced people on the juridical field like lawyers and bank workers, whose criteria was fundamental for the development of the juridical proposal. Finally, the conclusions and recommendations are presented, as well as the proposal of the reform consistent with the incorporation in the Monetary and Financial Organic Code of a chapter in which is included some norms for the management of the savings deposits